Ecological aspects of diet, reproduction, and parasitism of Pseudopaludicola boliviana (Anura, Leptodactylidae) from Corrientes, Argentina - Duré, Marta I.; Schaefer, Eduardo F.; Hamann, Monika I.; Kehr, Arturo I. (Phyllomedusa: Journal of Herpetology, 2004)
The main objectives of this paper were to update the distribution range of Pseudopaludicola boliviana in Argentina, to determine its diet composition and the feeding patterns, to analyze some reproductive variables as mature ova count and diameter in relation to female snoutvent length, to describe the advertisement call for Argentinean populations, and to identify and to localize its helminth parasites. Eleven prey types were identified; dipterans were more important both in number (23.53%) and in volume (41.30%); other important preys were collembolans, arachnids and coleopterans. The trophic niche width was 7.15 and the standardized trophic niche value was 0.61. Ovarian complement (number of mature ova for female) ranged from 50 to 319 (mean 175.3 ± 86.12), while ovum diameter ranged from 0.2 to 0.4 mm (mean 0.27 ± 0.062). The nuptial call is composed by five notes. The dominant frequency ranged from 3.488 to 5.927 kHz; emphasized frequency fluctuated between 4.942 and 5.224 kHz. A total of 10 helminth species (larvae and adults) were found in 54 (96%) infected frogs. Helminths were represented by Trematoda (7 species), Cestoda (1), Nematoda (1), and Acanthocephala (1).